Partnering Up: The Social Cognition of Partnered Interaction in Life and Art - Brown, Steven (Frontiers in Communication, 2022)
In this article, I present a model of social cognition that is grounded in the interplay between mentalizing and joint action during social interaction. I first propose a psychological distinction between a “character” and a “partner” as two different ways of conceiving of people in social cognition. A character is someone whom we connect with as a spectator. We can mentalize about them, but they cannot mentalize about us at the same time, since there is no direct interaction. A partner, by contrast, is someone with whom we are engaged in a social interaction such that the mentalizing is reciprocal. However, the defining feature of partnered interaction is not mentalizing per se but instead the adaptivity by which partners make ongoing behavioral adjustments to one another during their interactions. Such adaptivity provides a foundation for forming social bonds with people. I present a Dual Cohesion perspective that focuses on two complementary manners for achieving social cohesion with people during partnered interactions: alignment in conversation and entrainment in joint physical actions. Alignment is based on a cognitive convergence of ideas, whereas entrainment is based on a behavioral coordination of actions. Overall, the model reveals the interplay between mentalizing and joint action in social cognition and partnered interaction.